2018
DOI: 10.1097/nmd.0000000000000693
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Posttraumatic Stress and Depression Symptoms Among Syrian Refugees in a Refugee Camp

Abstract: Turkey is hosting the majority of Syrian refugees. The current study investigates the prevalence of probable posttraumatic stress disorder (PTSD) and depression among adult Syrians residing in a camp (N = 781) and potential predictors. The Impact of Event Scale-Revised was used to measure PTSD and the Beck Depression Inventory depression. Probable PTSD prevalence was 83.4%, with predictors being female sex (odds ratio [OR], 4.1), previous mental health problems (OR, 4.5), life threat (OR, 3.0), and injury of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
151
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(181 citation statements)
references
References 24 publications
22
151
7
1
Order By: Relevance
“…This is an area that requires further study – particularly with regards to the disproportionately high prevalence of mental health issues among forcibly displaced people (Bogic, Njoku and Priebe, ; Fazel, Wheeler and Danesh, ; Lindert et al, ). The most consistent factors linked to the prevalence of depression, anxiety and post‐traumatic stress disorder (PTSD) among war‐affected refugees are greater exposure to pre‐migration traumatic experiences, as well as post‐migration stress (Bogic, Njoku and Priebe, ; see also Acaturk et al, ). This shows that it is important that assistance in host communities does not further exacerbate the mental health crisis among war‐affected refugees.…”
Section: The Potential Of Cash Transfers To Facilitate Improvements Imentioning
confidence: 99%
“…This is an area that requires further study – particularly with regards to the disproportionately high prevalence of mental health issues among forcibly displaced people (Bogic, Njoku and Priebe, ; Fazel, Wheeler and Danesh, ; Lindert et al, ). The most consistent factors linked to the prevalence of depression, anxiety and post‐traumatic stress disorder (PTSD) among war‐affected refugees are greater exposure to pre‐migration traumatic experiences, as well as post‐migration stress (Bogic, Njoku and Priebe, ; see also Acaturk et al, ). This shows that it is important that assistance in host communities does not further exacerbate the mental health crisis among war‐affected refugees.…”
Section: The Potential Of Cash Transfers To Facilitate Improvements Imentioning
confidence: 99%
“…A recent study among Syrian refugees in the Netherlands found that 41% report psychological distress (Dagevos, Huijnk, Maliepaard, & Miltenburg, 2018). Studies among Syrian refugees in camp and non-camp settings in Europe report prevalence rates ranging from 14.5-44% for depression (Georgiadou, Zbidat, Schmitt, & Erim, 2018;Poole, Hedt-Gauthier, Liao, Raymond, & Bärnighausen, 2018), 13.5-92% for anxiety (Ben Farhat et al, 2018;Georgiadou et al, 2018) and 11.4-83.4% for PTSD (Acarturk et al, 2018;Georgiadou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many refugees are survivors of exploitation, torture, and sexual and gender-based violence, which further exacerbate their vulnerability to health conditions (Hassan et al, 2016). That said, they are less likely to receive mental health services because of social stigma, language and cultural barriers, imbalanced power dynamics with service providers, limited access to services, and low mental health literacy, have been reported as the most common mental health disorders among Syrian refugees (Acarturk et al, 2018;Georgiadou, Zbidat, Schmitt, & Erim, 2018), and they tend to be comorbid conditions. In the general population, MDD in particular, is the third leading cause of years lived with disability (YLDs) (IHME, 2020), and is considered a strong risk factor for suicide (May & Klonsky, 2016;Rogers, Ringer, & Joiner, 2018).…”
Section: Introductionmentioning
confidence: 99%